Organizational level factors of knowledge worker-workplace fit: Identifying the key drivers - Laura Gaižauskienė; Živilė Tunčikienė (Open Economics, 2018)
Nowadays there is bigger than ever mismatch between knowledge worker competencies and workplace requirements. In order to ensure a fit between these two elements, the concept of fit needs to be analysed from a different temporal perspective as well as different levels of the organization. The factors which affect the fit are identified using micro strategic human management system lens and two-periodical time division of time. When the fit is interpreted as the dynamic phenomenon, then it becomes the factor by itself to ensure organization level dynamic capabilities. The purpose of this article is to identify factors of knowledge worker-workplace fit. The methods used to reach the goal were analysed and synthesis of scientific literature were made.
Keywords: 330; competencies; dynamic capabilities; fit; knowledge worker; strategic human resource management; workplace